Ethnobotanical Studies of flora of Jebel Aulia district, Khartoum state with emphasis to toxicity of the common medicinal plants - Ali, Mozdelfa Adam Babiker; Ahmed, Haidar Abd Algadir Mohamed (Journal of agricultural, environmental and veterinary sciences, 2020)
Ethnobotany is the scientific study of the relationships that exist between people and plants. Ethnobotanists aim to document, describe and explain complex relationships between cultures and plants, focusing primarily on how plants are used, managed and perceived across human societies. This includes use for food, clothing, currency, ritual, medicine, dye, construction, cosmetics. Ethnobotanical studies are often significant in revealing locally important plant species especially for the discovery of crude drugs The documentation of traditional knowledge, especially on the medicinal uses of plants. has provided many important drugs of modern day. Out of the total flowering plants reported from the world, more than 50, 000 are used for medicinal purposes ( Govaerts, 2001 ). Extensive and intensive field trips were conducted to the study area during a course of two years from 2013 to 2015 representing several sites through Jebel Aulia district, Khartoum state. The study revealed a total of 117 species belonging to 100 genera and 45 families were recorded at Jebel Aulia locality. The family Poaceae was found to be the richest (13 species) followed by Ceasalpiniaceae, Euphorbiaceae, Mimosaceae (7 species) and Asteraceae (6 species). Herbs have dominated the vegetation of the study area (62. 40%) followed with trees (15. 40%), shrubs (8. 5%). Genus Euphorbia was considered as the most speciose (4 species) pursued with Senna and Ipomea which were represented by 3 species each. Tribulus longipetalus and Cyperus alopecuroides along with their Ethnomedicinal uses were documented for the first time. Fruits were the most commonly used plant part to prepare medicine followed with leaves and seeds. The main preparation methods of herbal remedies were infusion (25%) followed with decoction (14. 3%), edible (10. 7%) and pills (10. 7%). Oral administration was the most common route of herbal remedies within traditional medicine. Urinary tracts, kidney and abdominal complaints were the most frequent ailments traditionally healed. The source of medicinal plants was wild, (41. 66%), were cultivated (33. 34%) and (25%) were commercially bought from the market. Senna alexandrina was the most cited and important plant in the study area followed with Ziziphus spina-christi, Acacia nilotica, Solenostemma argel and Cymbopogon proximus. High informants consensus factor was indicated for Medicinal, furniture and food uses. Ziziphus spina Christi, Acacia senegal, Allium sativum and Cinnamomum verum have highest use-value ranging from (0. 062 to 0. 05). Cytotoxicity was evaluated using plants with a high relative frequency of citation. The results revealed that LC50 of water and ethanolic extracts of Acacia nilotica were more than 1000 µg/ml which considered not toxic and consequently safe at this dose. Whereas, water and ethanolic extracts of Senna alexandrina were less than LC 50 =256. 206 - 409. 6079 µg/ml. which is considered moderately toxic. Therefore, Senna extracts should be carefully used.
Keywords: Jabal Aulia; Khartoum State; plant toxicity; medicinal plants